Indonesian Mental Clause and Its Translation Directions in English - Made, Susini -; Sudipa, I Nengah; Suparwa, I Nyoman; Puspani, Ida Ayu Made (e-Journal of Linguistics; Vol 13 No 1 (2019): e-jl-January, 2019)
Abstract— Mental clause as a grammatical realization to express experience of the world of our consciousness is commonly found in a text of meditation. This type of text has orientation to persuade people to act in a particular way as suggested by the speaker or writer. This research is aimed at exploring how mental clause in Indonesian text is re-contextualized to convey the same meaning in English. The source language text is a text of meditation entitled Butir-Butir Kebijaksanaan: Titian Hidup Sehat dengan Meditasi Bio-Energi Ratu Bagus (Ida Pandita Mpu Nabe Parama Daksa Natha Ratu Bagus, 2012) and the target language text is its translation entitled Pearls of Wisdom: The Path of a Healty Life with Ratu Bagus Bio-Energy Meditation (Stacey, 2014). Drawing translation as re-contextualization (House, 2015), Systemic Functional Linguistics (Halliday, 2014) and translation strategies (Malone, 1988), this study focuses on the directions of mental clause in Indonesian-English translation and the translation strategies inducing the directions. The research result shows that mental clause of the Indonesian text can be rendered into various clause types which include mental clause and non-mental clause. It can also be rendered into a form of nominalization. The strategies which condition the directions include strategy of equation, reordering, diffusion and condensation .